Selective P-C bond cleavage of tertiary phosphine boranes by sodium. (2nd November 2021) - Zhang, Jian-Qiu; Ye, Jing-Jing; Han, Li-Biao
Abstract: Herein reported is the facial modification of tertiary phosphine boranes R3 PBH3 by selective cleaving the P-Ph bond by sodium in which the phosphide borohydride R2 PNa(BH3 ) is quantitatively generated and could be easily quenched by electrophiles to furnish a series of new phosphine boranes in high yields. Graphical Abstract: UF0001